2012
DOI: 10.1371/journal.pone.0045693
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Inflammation, Adiponectin, and Oxidative Stress in Metabolic Syndrome

Abstract: Metabolic syndrome (MS) represents a cluster of physiological and anthropometric abnormalities. The purpose of this study was to investigate the relationships between the levels of inflammation, adiponectin, and oxidative stress in subjects with MS. The inclusion criteria for MS, according to the Taiwan Bureau of Health Promotion, Department of Health, were applied to the case group (n = 72). The control group (n = 105) comprised healthy individuals with normal blood biochemical values. The levels of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 29 publications
9
78
0
3
Order By: Relevance
“…26) Additionally, a significant correlation between adiponectin, inflammatory markers and oxidative stress has been observed in patients with metabolic syndrome. 27) Liraglutide has been reported to significantly increase plasma adiponectin levels and adiponectin protein expression in adipose tissue in the mice with high fat diet-induced NAFLD. 28) However, whether liraglutide can also elevate the adiponectin levels in the liver is not yet established.…”
mentioning
confidence: 99%
“…26) Additionally, a significant correlation between adiponectin, inflammatory markers and oxidative stress has been observed in patients with metabolic syndrome. 27) Liraglutide has been reported to significantly increase plasma adiponectin levels and adiponectin protein expression in adipose tissue in the mice with high fat diet-induced NAFLD. 28) However, whether liraglutide can also elevate the adiponectin levels in the liver is not yet established.…”
mentioning
confidence: 99%
“…As a consequence, the oxidative stress generated by the severe inflammation contributes to valve damage [5]. A study by Chen et al (2012) showed that the increased inflammation was significantly correlated to the increase of oxidative stress. Under stressful conditions such as inflammatory processes mediated by oxidative stress, the cell surface undergo glycosylation and thus can be targeted in MBL/ficolin binding.…”
Section: Discussionmentioning
confidence: 99%
“…Under stressful conditions such as inflammatory processes mediated by oxidative stress, the cell surface undergo glycosylation and thus can be targeted in MBL/ficolin binding. This in turn will lead to pathological complement activation, and inflammation [26]. In vitro studies showed that oxidative stress caused formation of MBL ligand activating complement in the endothelial cells [2].…”
Section: Discussionmentioning
confidence: 99%
“…В Україні також третина насе-лення хворіє на ГХ [4,5]. На сучасному етапі доведе-ний зв'язок НАЖХП з ГХ, а сам факт розвитку зазна-ченої патології змінює прогноз для таких пацієнтів як щодо прогресування печінкової недостатності, так і в плані значного підвищення частоти ускладнень серцево-судинних захворювань (ССЗ).…”
Section: вступunclassified